Theoretical Study of Dual-Function Sensor for Analysis of Blood Composition and Glucose Concentration Based on Nonreciprocal Analog of the Electromagnetically Induced Absorption - Wan, Bao-Fei; Li, Bing-Xiang; Zhang, Hai-Feng (IEEE transactions on instrumentation and measurement, 2023)
A nonreciprocal biosensor for the detection of different liquid substances is proposed based on an analog of the electromagnetically induced absorption (EIA-like) effect. Different bright-mode and dark-mode coupling structures are designed for the forward and backward incidences, respectively, and as a result, the incisive EIA-like peaks are staggered at different frequency points. The regulation of nonreciprocal EIA-like effects by the shifts of metal thickness and incident angle is discussed. The EIA-like peaks in different directions occupy different measurement ranges (MRs) and detection capabilities, so they are suitable for detecting blood components and glucose concentrations, accordingly. Multiple layers of analyte cavities are introduced to increase the sensitivity ([Formula Omitted]) of the sensor. For the forward incidence, the [Formula Omitted] of the measurement after fitting the response frequency points under different blood components is 190.85 THz/RIU, the figure of merit (FOM) is 367.02, and the detection limit (DL) is [Formula Omitted]. For the detection of glucose solution concentration of 0–350 g/L at the backward incidence, the corresponding indicators are 337.46 THz/RIU, 1297, and [Formula Omitted] (0.32 g/L). The interferences of the thickness error of the analyte cavity on the sensor are also explored.